2005
DOI: 10.1086/427956
|View full text |Cite
|
Sign up to set email alerts
|

Mutations that Cause Osteoglophonic Dysplasia Define Novel Roles for FGFR1 in Bone Elongation

Abstract: Activating mutations in the genes for fibroblast growth factor receptors 1-3 (FGFR1-3) are responsible for a diverse group of skeletal disorders. In general, mutations in FGFR1 and FGFR2 cause the majority of syndromes involving craniosynostosis, whereas the dwarfing syndromes are largely associated with FGFR3 mutations. Osteoglophonic dysplasia (OD) is a "crossover" disorder that has skeletal phenotypes associated with FGFR1, FGFR2, and FGFR3 mutations. Indeed, patients with OD present with craniosynostosis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
198
0
5

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 294 publications
(218 citation statements)
references
References 30 publications
11
198
0
5
Order By: Relevance
“…36 It is possible that the systemic overexpression of α-Klotho in this patient might set the stage for an FGF23-FGFR1 autocrine loop to be established in FGF23-secreting cells, such as osteocytes. In addition, the FGFR1 signaling could mediate the upregulation of FGF23 in osteocytes, [37][38][39][40][41] thereby exerting a positive feedback mechanism, with creation of a self-sufficient cellular environment and eventual formation of highly FGF23-secreting tumors, ie, phosphaturic mesenchymal tumors. This could explain why this patient would have two such rare tumors.…”
Section: Discussionmentioning
confidence: 99%
“…36 It is possible that the systemic overexpression of α-Klotho in this patient might set the stage for an FGF23-FGFR1 autocrine loop to be established in FGF23-secreting cells, such as osteocytes. In addition, the FGFR1 signaling could mediate the upregulation of FGF23 in osteocytes, [37][38][39][40][41] thereby exerting a positive feedback mechanism, with creation of a self-sufficient cellular environment and eventual formation of highly FGF23-secreting tumors, ie, phosphaturic mesenchymal tumors. This could explain why this patient would have two such rare tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, homologous mutations in FGFR1 (Y372C), FGFR2 (Y375C) and FGFR3 (Y373C) were identified and cause various osteogenic deficiency syndromes (Wilkie, 2005). It was shown that FGFR1 Y372C (White et al, 2005) and FGFR3 Y373C (d 'Avis et al, 1998) are constitutively activated in vitro. For the FGFR3 Y373C mutation, the oncogenic potential was shown and it was suggested that this mutation contributes to the tumour progression of multiple myeloma (Chesi et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The functions of FGFR1 signaling in hypertrophic chondrocytes are not entirely understood due to imprecise genetic tools and difficulties in distinguishing cell-autonomous functions in hypertrophic chondrocytes from activities in the adjacent perichondrium and other tissues. Activating mutations in FGFR1 that cause osteoglophonic dysplasia result in severe dwarfism in humans (White et al 2005); however, an activating mutation in Fgfr1 in mice did not affect endochondral ossification (Zhou et al 2000). Possible functions of FGFR1 signaling have been investigated in mice through targeted inactivation of Fgfr1 (Col2a1-Cre or Dermo1-Cre).…”
Section: Intramembranous Mesenchymal Condensationsmentioning
confidence: 99%